Toxicity of Organophosphorus Flame Retardants: Implications in Environmental Persistence - Howell, Bob A. (Recent Developments in Chemistry and Biochemistry Research Vol. 3, 2024)
Organophosphorus flame retardants (OPFRs) are high-production volume chemicals. Recent reports reveal that OPFRs are ubiquitous in the environment. Unfortunately, the toxicity profiles for OPFRs on organisms remain limited. Concerns over possible toxicity are growing as organophosphorus flame retardants have been developed and used more frequently. The majority of research on possible toxicity to date has concentrated on simple phosphate esters, which can comprise aryl, alkyl, or even halogenated phosphate esters in certain situations (which belong more appropriately in the category of organohalogen flame retardants). The inclusion of several kinds of esters into a single study leads to muddled conclusions. Each class of phosphate esters should be subjected to toxicity assessment separately. Further, the potential toxicity of the more effective (lower level of oxygenation at phosphorus: phosphonates, phosphinates, phosphine oxides) organophosphorus flame retardants has been little explored. The few results available suggest that these compounds exhibit no or minimal toxicity (lower than that of phosphates). This represents an area that should be the focus of careful detailed studies to establish any potential toxicity. Studies of the toxicity of phosphonates, phosphonites and phosphine oxides, as separate classes, should be conducted. Reliable toxicity data for organophosphorus compounds as a function of structure are needed.